Novel kidney dissociation protocol and image-based flow cytometry facilitate improved analysis of injured proximal tubules - Manolopoulou, Marika (Am J Physiol Renal Physiol, 2019)
Flow cytometry studies on injured kidney tubules are complicated by the low yield of nucleated single cells. Furthermore, cell-specific responses such as cell cycle dynamics in vivo have conventionally relied on indirect immunohistochemistry and proximal tubule markers that may be downregulated in injury. Here, we report a new tissue dissociation protocol for the kidney with an early fixation step that greatly enhances the yield of single cells. Genetic labeling of the proximal tubule with either mT/mG “tomato” or R26Fucci2aR (Fucci) cell cycle reporter mice allows us to follow proximal tubule-specific changes in cell cycle after renal injury. Image-based flow cytometry (FlowSight) enables gating of the cell cycle and concurrent visualization of the cells with bright field and fluorescence. We used the Fucci mouse in conjunction with FlowSight to identify a discrete polyploid population in proximal tubules after aristolochic acid injury. The tissue dissociation protocol in conjunction with genetic labeling and image-based flow cytometry is a tool that can improve our understanding of any discrete cell population after injury.